Influence of Instructional Language on Comprehension of Science Concepts among Learners - Ankudze, Mercy (My University, 2024)
Many sub-Saharan African countries of which Ghana is no exception are still bedeviled by the language of instruction in Education policy and how to manage both L1 and L2 instruction. In Ghana, the educational policy does not allow using L1 as a medium of instruction beyond basic school three (B3). Although numerous studies have called for extensive use of L1 as a medium of instruction, stringent and robust educational policy cannot be formulated until practical and contextualised studies are conducted. In this study, the influence of L1 on the comprehension of science concepts by learners in the upper basic school is studied in the Effutu municipality of Ghana. A quasi-experimental method was employed as the research design for the study. The population was primary school students from Effutu municipality in the Central region of Ghana. Two basic five (B5) classes were purposively selected, and data were collected using interviews as the main instrument. The data were analysed and presented using descriptive statistics. The finding from the study showed that L1(Fante) influences and enhances the comprehension of science concepts of basic five (B5) students in the Effutu municipality of Ghana. However, instructional challenges may be faced while teaching respiration and sensitivity science concepts as concepts with sufficient Fante vocabulary to express them were easily comprehended in English compared to concepts with fewer Fante vocabulary. Therefore, it is suggested that expanding L1(Fante) vocabulary by coining and transliterating new words could aid in effectively teaching all science concepts.
Keywords: Instructional language, Comprehension, Science Concepts, First language, Second language, Ghana